CEO Activism and the Backfire Effect: Lessons from Erspo’s Reputational Crisis and the Mechanics of Digital Spillover - Rani amartha Aurelia; Irvani Saputri; Naswa aulia Rahmawati; Pramudya Ibnu Subrata (CITACONOMIA : Economic and Business Studies, 2026)
The digital landscape of 2026 has witnessed a fundamental transformation in public relations, where the Chief Executive Officer (CEO) serves as a symbolic manifestation of corporate identity. This conceptual article examines the "reputational spillover" phenomenon, where an executive’s personal digital behavior directly impacts institutional legitimacy. Using a descriptive qualitative method and a literature study approach, this research analyzes the communication crisis of the sportswear brand Erspo (2024-2025). The study identifies that the crisis escalated from technical product criticism to a systemic character crisis due to the leader's defensive and confrontational social media responses. Findings reveal that in identity-driven markets like Indonesia, digital arrogance from leadership triggers collective anger, especially when national symbols are involved. This research proposes the "Empathy-First" Model, which advocates for the separation of personal communication authority and official corporate channels during a crisis. Furthermore, the study introduces the concept of PR Governance for Executives, emphasizing digital humility and emotional intelligence as essential safeguards against "cancel culture." Ultimately, the article concludes that institutional stability in the digital era depends on the leader's ability to synchronize their digital persona with public ethical expectations, transforming potential crises into opportunities for strengthening stakeholder trust.